The Impact of The Rural Culture and Cultural Attractions on Poverty Alleviation : The Moderating Effect of Tourism Resources - Komathi, Wasudawan; Mahani, Mohammad Abdu Shakur; Rossazana Ab-Rahim, Ab-Rahim (Human Resource Management Academic Research Society, 2021)
This study aims to investigate the impact of rural culture and cultural attractionson poverty alleviation and the moderating effect of tourism resources on rural, culture, wildlife, nature and physical. Convenience sampling was applied in selecting 520 respondents. The Statistical Package for Social Science was used to analyse the descriptive statistic while Partial Least Square-Structural Equation Modelling (SEM) was used to analyse the hypotheses. The results show both rural culture and cultural attractions have a positive effect onpoverty alleviation. Besides, tourism resources have a positive moderating effect on rural culture and poverty alleviation. Poverty reduction through tourism, communities right to use tourism resources and accommodate different cultural views are supported by Human Development Theory on the positive findings. However, tourism resources a negative result on cultural attractions and poverty alleviation. Therefore, this study suggests that preserving cultural attractions such as cultural buildings, landscapes, monuments, traditions, arts, crafts, food, and customs should be encouraged for socio-economic benefits.